Workhshop Kiat-kiat Penulisan Jurnal Internasional (Mengenal Jurnal Internasional Pendidikan Matematika) - Rizki, Lussy Midani; Nur Utami , Dwike; Erlangga, Putri; Yusri Farmansyah , Riski (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
This service activity aims to socialize tips for writing international journals and introduce international journals for mathematics education for mathematics education student. The service method is divided into three stages, namely the preparation stage, the implementation stage, and the reporting stage. Based on the stages of activities that have been planned, community service activities are produced, such as: (1) the preparatory stage is to produce materials and community service instruments. The material produced is in the form of international journal tips, and getting to know international journals in mathematics education. In addition, the resulting instrument is a participant response questionnaire which will be given at the end of the activity; (2) the implementation phase resulted in the introduction of international journals, international journals for mathematics education, and the requirements for writing international journals (3) the reporting stage resulted in an analysis report and evaluation of all processes of community service activities. In conclusion, the results of the dedication show that the students are very happy and well received, so that this workshop has been able to provide a clear picture regarding the tips of international journals (know international journals for mathematics education. Finally, students are expected to be able to get to know international journals for mathematics education well and right.